ANALYSIS OF CAESAREAN SECTION RATES USING THE ROBSON’S TEN GROUP CLASSIFICATION SYSTEM (TGCS) AT TERTIARY LEVEL HEALTHCARE FACILITIES IN RAWALPINDI, PAKISTAN: A CROSS-SECTIONAL STUDY - Chaudhri, Rizwana; Hanif, Kauser; Humaira Bilquis; Ezra Reza, Tahira; Uzma, Qudsia; Khan, Ammarah; Aabroo, Atiya; ur Rehman, Fazal; Emmanuel, Faran (Journal of Ayub Medical College Abbottabad, 2025)
Background: Robson’s Ten Group Classification System (TGCS) is recommended as a global standard for assessing, monitoring, and comparing Cesarean Section rates at all levels. This study was conducted to audit CS deliveries using the Robson TGCS to understand the current CS practices and analyze the groups of women who are mainly contributing to the rising rates of CS in Pakistan. Methods: A cross-sectional study was conducted in three tertiary care hospitals in Rawalpindi, Pakistan. All women who gave birth in these health facilities between, June to August 2019, were included in the study. Data were collected using a standardized proforma and analyzed using Robson guidelines to calculate each group’s relative size, group-specific CS rate, and relative and absolute group contributions toward overall Caesarean section rates. Results: A total of 5,657 deliveries were analyzed. Out of these, 2255 (40%) were Cesarean sections. Women in Group 3 made the largest contribution to the obstetric population accounting for 26.3% of all deliveries. The largest contributors to the overall CS rate were Group 5 (41.7 %), Group 10 (17.3%), and Group 2 (12.7%). Conclusion: A CS rate of 39.9% was reported, which is much higher than the WHO recommended optimal rate of CS. Group 5 (previous CS) was found to be the largest contributor to the overall CS rates followed by Group 10. This study provides a model for institutionalizing RTGCS and should be replicated in other districts of Pakistan.